2018
DOI: 10.11114/jets.v6i9.3345
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Somatotype Structures in Students Studying at Different Departments of Physical Education

Abstract: This study aims to analyze the somatotype structures in students studying at different departments of physical education. A total of 300 male students (elite-sub-elite athletes) who study physical education and sports (n=100), coaching education (n=100) and sports management (n=100) at School of Physical Education and Sports at University of Kirsehir Ahi Evran voluntarily participated in this study. Somatotype structures were determined using Heath-Carter method and SOMATOTURK calculation program. SPSS 22.0 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The classification of males was predominantly mesomorphic with a secondary endomorphic component, while females were primarily endomorphic with a secondary mesomorphic component. Other studies have found similar results [34][35][36][37], though asymmetry level was not considered. Table 3.…”
Section: Discussionmentioning
confidence: 62%
“…The classification of males was predominantly mesomorphic with a secondary endomorphic component, while females were primarily endomorphic with a secondary mesomorphic component. Other studies have found similar results [34][35][36][37], though asymmetry level was not considered. Table 3.…”
Section: Discussionmentioning
confidence: 62%
“…The endomorph somatotype is dominant in the average woman, especially if she is not involved in sports while in men the mesomorph dominates. Many studies confirm that women are predominantly endomorphic with a secondary mesomorphic component [48][49][50]. 4).…”
Section: Weights and Biasesmentioning
confidence: 98%
“…In addition, quantitative assessment of physical condition provides valuable information about physical health and functional capabilities of the body. It allows to adjust the volume of organized physical activity and planning of certain physical activities in the educational process [1,8,10,11].…”
Section: Introductionmentioning
confidence: 99%